Application of Mobile Geographic Information System Platform in High Voltage Grid Planning. (June 2020) - Zhang, Qianmao; Liu, Rui; Qi, Xiaoguang; Xi, Peng
Abstract: Grid planning and pre-project site survey require the support of Geographic Information System (GIS). However, the existing grid GIS platform adopts B/S mode which can only be run and viewed on the computer connected to the company's intranet, thus failing to meet the needs of on-site investigation by the planners. Therefore, the application of mobile GIS platform to pre-grid planning is an inevitable development direction for the future power grid information system, and how to manage more efficiently and use the data collected by mobile GIS terminal will be an urgent problem to be solved. Based on the authors' learning and practical experience, this work first analyzed the potentials of mobile GIS for grid planning, then discussed the problems in high voltage grid planning, and finally proposed the system function and overall architecture design based on mobile GIS platform.